Enhancing Numeracy in Young Children through a Parenting Intervention - Kristina Nicole Higgins (Social Welfare: Interdisciplinary Approach, 2021)
Children who enter a formal setting with a deficit in mathematics carry this deficit throughout their schooling (Galindo & Sonnenschein, 2015), and an early understanding of mathematical language is foundational for later mathematical understanding (Jamison, 2000). This study seeks to increase the mathematical language and interactions in the home prior to children entering kindergarten by providing parents with both mathematical activities and specific instructions related to each activity. Forty families with children ages three to five years old participated in a single group pretest-posttest study where hands-on mathematical activities were sent home each week for fifteen weeks. Parents completed an assessment of current home numeracy and expectations for the end of kindergarten, and children completed an assessment of mathematical understanding. Results indicate an increase in some areas of current home numeracy, parental expectations, and children’s mathematical understanding over and above maturation. Findings, limitations, and implications for future research will be discussed.